2015
DOI: 10.1371/journal.pone.0139287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LiF:Mg,Ti (TLD-100) for Intraoperative Electron Radiation Therapy Quality Assurance

Abstract: BackgroundPurpose of the present work was to investigate thermoluminescent dosimeters (TLDs) response to intraoperative electron radiation therapy (IOERT) beams. In an IOERT treatment, a large single radiation dose is delivered with a high dose-per-pulse electron beam (2–12 cGy/pulse) during surgery. To verify and to record the delivered dose, in vivo dosimetry is a mandatory procedure for quality assurance. The TLDs feature many advantages such as a small detector size and close tissue equivalence that make t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…This result was in line with the well-known published results 22,23 and with the findings of our previous work. 14 In addition, a recent study was carried out by Bahreyni Toossi et al 24 about calibration of TLDs with 6-MV photon and 6-MeV electron irradiation but restricted to the dose range 0 to 2 Gy. The results of the study showed that for dose up to 120 cGy the TLD response is linear and for higher dose supralinear, for both types of radiation beams.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in line with the well-known published results 22,23 and with the findings of our previous work. 14 In addition, a recent study was carried out by Bahreyni Toossi et al 24 about calibration of TLDs with 6-MV photon and 6-MeV electron irradiation but restricted to the dose range 0 to 2 Gy. The results of the study showed that for dose up to 120 cGy the TLD response is linear and for higher dose supralinear, for both types of radiation beams.…”
Section: Discussionmentioning
confidence: 99%
“…We experienced the latter problem when we tried to measure using two MOSFETs at the same time, as reported in the results section. The difficulty of inserting more than one MOSFET has also been identified elsewhere [ 24 ]. In addition, it has been pointed out that MOSFETs are presumably more difficult for the surgeon to initially handle because they have to be inserted with sterile components and attached onto the surgical bed [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the 1990s, dedicated mobile linacs, characterized by output rates of 2 to 12 cGy per pulse, were developed and introduced [ 4 ]. The high dose-per-pulse reduces the irradiation time during the surgery because 10 Gy are typically delivered in less than 1 min [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thermoluminescent response is not linear for large doses. At high doses, above 10 Gy, it exhibits a supralinear behaviour; this supralinearity has been one of the main drawbacks to their use in high-dose dosimetry (Liuzzi et al, 2020;Liuzzi, Savino, D'Avino, Pugliese, & Cella, 2015). For this reason, a smaller dose was given (with scaled monitor units from the original treatment plan) via the same treatment machine.…”
Section: Ta B L Ementioning
confidence: 99%